2016
DOI: 10.1186/s12885-016-2113-8
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine in the routine first-line treatment of elderly patients with advanced colorectal cancer - results from a non-interventional observation study

Abstract: BackgroundThe purpose of this observational study was to evaluate feasibility, efficacy results and toxicity observations of capecitabine in routine first line treatment of patients with metastatic colorectal cancer, with particular regard of elderly patients (>75 years of age).MethodsPatients with colorectal cancer receiving capecitabine as part of their first-line treatment were recorded until detection of disease progression or up to a maximum of 12 cycles on standardized evaluation forms. Additional inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
2
9
0
1
Order By: Relevance
“…The rates of adverse events reported in this study are similar to those of reported clinical trials of capecitabine monotherapy. The rate of HFS in this study (46.5% overall) is consistent with rates observed in phase III clinical trials of 30–53.5% [ 4 , 8 , 10 ] and with the rate of 42% reported in an observational study that included patients who received capecitabine as monotherapy or in combination treatment [ 14 ]. The rate of GI events in this study was 44.2%; previous studies have reported that between 11 and 50% of patients experience one GI event, including diarrhea, vomiting, nausea, or abdominal pain, while receiving capecitabine monotherapy [ 4 , 8 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The rates of adverse events reported in this study are similar to those of reported clinical trials of capecitabine monotherapy. The rate of HFS in this study (46.5% overall) is consistent with rates observed in phase III clinical trials of 30–53.5% [ 4 , 8 , 10 ] and with the rate of 42% reported in an observational study that included patients who received capecitabine as monotherapy or in combination treatment [ 14 ]. The rate of GI events in this study was 44.2%; previous studies have reported that between 11 and 50% of patients experience one GI event, including diarrhea, vomiting, nausea, or abdominal pain, while receiving capecitabine monotherapy [ 4 , 8 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our analysis, the occurrence of HFS and GI events was not related to the dose of capecitabine, which may suggest that lower starting doses and dose reductions do not improve adverse event rates, nor do they prevent them from occurring. In an observational study by Stein et al, the incidence of HFS increased with duration of treatment and was higher in younger patients than in older patients (46 vs. 37%; p = 0.0014) despite similar median daily doses of capecitabine [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall response rate (ORR) was significantly increased in the patient group ≤75 years compared to patients >75 years of age (38 vs. 32%, p=0.019). Median progression free survival (PFS; 9.7 vs. 8.2 months, p= 0.00021) and overall survival (OS; 31.0 vs. 22.6 months, p<0.0001) was decreased in elderly patients (24). In a phase II trial of 51 patients aged >70 years with advanced CRC, capecitabine was effective and well tolerated, with an ORR of 24%, PFS of 7 months and OS of 11 months.…”
Section: Discussionmentioning
confidence: 99%